Assessing the downstream socioeconomic impacts of agroforestry in Kenya - Hughes, K.; Morgan, S.; Baylis, K.; Oduol, J.; Smith-Dumont, E.; Vågen, Tor-Gunnar; Kegode, H. (Elsevier, 2020)
Agroforestry is widely purported to improve the livelihoods of smallholder farmers, rehabilitate degraded landscapes, and enhance the provisioning of ecosystem services. Yet, evidence supporting these longer-term impacts is limited. Using a quasi-experimental impact evaluation design informed by a theory-based and mixed methods framework, we investigated selected intermediate and final outcomes of a nine-year effort led by Vi Agroforestry, a Swedish non-governmental organization (NGO), to promote agroforestry in large sections of Bungoma and Kakamega counties in western Kenya. We compared households belonging to 432 pre-existing farmer groups operating in 60 program villages and 61 matched comparison villages. To address potential self-selection bias, we used program targeting as an instrument for program participation, combined with the difference-in-differences approach to control for time-invariant differences between our treatment and comparison groups. We complemented the above with semi-structured interviews with a sub-sample of 40 purposively selected program participants. Despite evidence of variable program exposure and agroforestry uptake, we found modest, yet statistically significant, effects of Vi Agroforestry’s program on intermediate outcomes, such as agroforestry product income, fuelwood access, and milk yields among dairy farmers. We also found that this program modestly increased asset holdings, particularly among households represented by female program participants.